2020
DOI: 10.4049/jimmunol.2000132
|View full text |Cite
|
Sign up to set email alerts
|

Chaperone-Mediated Autophagy Suppresses Apoptosis via Regulation of the Unfolded Protein Response during Chronic Obstructive Pulmonary Disease Pathogenesis

Abstract: Cigarette smoke (CS) induces accumulation of misfolded proteins with concomitantly enhanced unfolded protein response (UPR). Increased apoptosis linked to UPR has been demonstrated in chronic obstructive pulmonary disease (COPD) pathogenesis. Chaperone-mediated autophagy (CMA) is a type of selective autophagy for lysosomal degradation of proteins with the KFERQ peptide motif. CMA has been implicated in not only maintaining nutritional homeostasis but also adapting the cell to stressed conditions. Although rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 42 publications
2
23
0
Order By: Relevance
“…In addition, an inhibitory role for CMA in CS extract (CSE)-induced epithelial cell apoptosis has been reported for immortalized BEAS-2B bronchial epithelial cells [64]. Our in vitro experiments have shown that CSE induces CMA activation of LAMP2A expression through Nrf2-regulated transactivation [13]. CMA inhibition enhances the UPR, accompanied by increased apoptosis in response to CSE exposure, which is clearly reversed by LAMP2A overexpression in human bronchial epithelial cells (HBECs), indicating functional crosstalk between UPR and CMA during CSE exposure [13].…”
Section: Cma In Copd Pathogenesissupporting
confidence: 58%
See 2 more Smart Citations
“…In addition, an inhibitory role for CMA in CS extract (CSE)-induced epithelial cell apoptosis has been reported for immortalized BEAS-2B bronchial epithelial cells [64]. Our in vitro experiments have shown that CSE induces CMA activation of LAMP2A expression through Nrf2-regulated transactivation [13]. CMA inhibition enhances the UPR, accompanied by increased apoptosis in response to CSE exposure, which is clearly reversed by LAMP2A overexpression in human bronchial epithelial cells (HBECs), indicating functional crosstalk between UPR and CMA during CSE exposure [13].…”
Section: Cma In Copd Pathogenesissupporting
confidence: 58%
“…A recent paper has demonstrated that Nrf2 upregulates LAMP2A expression levels by binding to the LAMP2A gene [25], which may at least partly explain the mechanism for CMA activation during oxidative stress. We have also detected the participation of Nrf2-mediated LAMP2A expression in cigarette smoke (CS)-induced CMA activation [13]. Alternatively, increase in LAMP2A levels is also mediated through alterations of protein stability in starvation conditions.…”
Section: Mechanisms Of Cmamentioning
confidence: 91%
See 1 more Smart Citation
“…An annexin V-fluorescein isothiocyanate (FITC) apoptosis detection kit (BD Biosciences) was used for apoptosis evaluation as described previously [47]. Apoptotic cells were analyzed using a FACSCalibur flow cytometer (BD bioscience) and reported as the percentage of cells showing annexin V+/propidium iodide (PI)-and annexin V+/PI+.…”
Section: Isolation Of Neutrophils and Eosinophils And Western Blottingmentioning
confidence: 99%
“…Interestingly, another form of autophagy known as chaperonemediated autophagy (CMA), which is LAMP2A facilitated selective degradation of proteins containing Lys-Phe-Gln-Arg-Gln (KFERQ) in the lysosomes mitigates cigarette smoke induced UPR and apoptosis (72).…”
Section: Chronic Obstructive Pulmonary Diseasementioning
confidence: 99%